2015
DOI: 10.1007/s12262-015-1298-4
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Registry Development for Jos University Teaching Hospital: Report of the First Year Experience

Abstract: Adequate intervention in trauma management and prevention requires a well-documented database for objective study of the disease characteristics, hence the need for a trauma registry. The aim and objective of this study is to document in a database all patients admitted in our hospital following trauma. This study was conducted at the Jos University Teaching Hospital, Jos, Plateau State, Nigeria. Beginning 1 January 2012, data was collected on a trauma data sheet and transferred to a 3-page, 80-point questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Barriers relating to both staffing and funding the trauma registry emerged as the first and second most common issues from respondents respectively, and is supported readily by papers that have documented or reported on their individual experience of trauma registry implementation [22][23][24][25][26] . A study by O'Reilly et al (2016), which reported the lessons learned of trauma registry development in both HICs and LMICs similarly identified both funding and staffing challenges as key topics to surface in their interviews with trauma registry custodians.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers relating to both staffing and funding the trauma registry emerged as the first and second most common issues from respondents respectively, and is supported readily by papers that have documented or reported on their individual experience of trauma registry implementation [22][23][24][25][26] . A study by O'Reilly et al (2016), which reported the lessons learned of trauma registry development in both HICs and LMICs similarly identified both funding and staffing challenges as key topics to surface in their interviews with trauma registry custodians.…”
Section: Discussionmentioning
confidence: 99%
“…(mean age of 29 ± 15 years) based on trauma registry data from a center in Northern Nigeria. [ 9 10 ] However, the two studies under reference included data from both children and adults, while our study was restricted to adults. This may account for the downward pull on the mean in the other studies.…”
Section: Discussionmentioning
confidence: 99%
“…(Lagos) – 2.3%. [ 10 11 12 ] The findings by Cassidy et al . may not be representative of the country because it included findings from Abuja, the Federal Capital Territory, which being the seat of Government, may enjoy more facilities than most other States or regions of the country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations